Pendekatan Multikultural Dalam Pembelajaran Pendidikan IPS - Edi Susrianto Indra Putra (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Indragiri (UNISI), 2023)
A multicultural approach is an understanding of looking at the various variations that exist in Indonesian society. This diversity is described in various forms such as ethnicity, culture, language, customs and religion. By understanding these differences, it is hoped that students will understand and become a great force as a glue for the nation. The multicultural approach is a cross-border discourse. In a multicultural approach it is related to issues of social justice, democracy and human rights. It is not surprising that multicultural education is closely related to political, social, cultural, moral, social strata and religious issues. The method used in this research is a qualitative method, with the type of library research, a series of research through library data collection. The approach used in this research is a philosophical and pedagogical approach. A multicultural approach is the development of curriculum and educational activities to tap into a variety of views, histories, and concerns for other people. Meanwhile, broadly the multicultural approach covers all students without distinguishing between groups such as gender, ethnicity, race, culture, social strata and religion. Multicultural views must be reflected in social studies education learning.